Total synthesis of argyrin A and analogues thereof - Chen, Chou-Hsiung (2013)
The cyclin dependent kinase inhibitor p27 is one of the most frequently dysregulated tumour suppressor protein in human cancers. A reduction in the level of cellular p27 is frequently due to increased proteasome-dependent degradation. Recently, studies show that the macrocyclic octapeptide argyrin A induced an increase in cellular p27 levels by preventing the turnover of the protein via inhibition of proteasome function. In order to investigate this interesting biological property, this project embarked on the total synthesis of argyrin A, a naturally occurring macrocyclic peptide originally isolated from myxobacteria Archangium gephyra. Argyrin A is a non-ribosomal octapeptide containing four standard amino acids and three unusual amino acid-based subunits. The synthesis of these three unusual amino acid components was established. In particular, a novel generic synthetic route to access the optically pure N-Fmoc-4-methoxy-tryptophan and analogues thereof was developed. Key features of the synthetic route include the use of chiral Strecker amino acid synthesis and mild conditions to hydrolyse α-amino nitrile to α-amino acid. Furthermore, the total synthesis of argyrin A and analogues was accomplished by the application of modern solid-phase chemistry and macrocyclisation strategies. This platform technology will enable the robust total chemical synthesis of a focused library of argyrin analogues, which will facilitate a comprehensive SAR study. Additionally, the synthesised argyrin A and analogues thereof comprising unique tryptophan analogues were tested in a cytotoxicity assay against HCT-117 human colon cell line. The results showed that all synthetic argyrin derivatives display growth inhibitory effects at nanomolar concentrations. The best result was obtained for the argyrin A and (5-methoxy-Trp4)argyrin with GI50 value at 1.8 and 3.8 nM, respectively. In summary, it became apparent that the methoxy group at 4- or 5-position of tryptophan-5 residue is essential for the biological activity of argyrin.